From Colonial to Digital Resistance: The Leadership Transformation in Information-Driven Political Struggles - Sutanto, Rudy; Cyprien, Genie; Praditama, Angger Gilang; Iqbal, Muhammad (Jurnal Studi Pemerintahan, 2026)
Leadership in political mobilisation under asymmetrical conditions is determined by informational conditions. Existing research has focused on organisational power, networking and digital possibilities but less on conditions of information-poor leadership. To fill this gap, the research reconceptualises leadership as information-based and links historical and contemporary studies on resistance. In this paper, we use a qualitative interpretive approach and secondary historical data as a foundation for studying Supriyadi in the PETA Blitar rebellion. It demonstrates that when there is a lack of information, leadership is built on amiable selectivity, segmentation and secrecy to create networks that are fragmented yet trust-based. However, when there is too much information there is a transformation in leadership into managing public perceptions, content creation and getting used to living in an environment where everything is algorithm-driven. However, while these differences vary one thing remains constant: leadership is ultimately about control of information in hierarchical structures. This paper offers: reaffiliation of leadership with information practices; visualising leadership as a condition to build networks through control of information; and an intersection of historical and digital insights on resistance. It offers a theory of leadership in varying informational contexts.